Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1371/journal.pone.0268578
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of the cancer patients receiving home-based palliative care in Dhaka city of Bangladesh

Abstract: Background The concept of home-based palliative care has been recently introduced in Bangladesh, but the patients’ quality of life remains unexplored. This study aimed to assess the quality of life and its determinants of the cancer patients receiving home-based palliative care in Dhaka, Bangladesh. Methods This cross-sectional study was conducted among 51 surviving cancer patients above 18 years registered under the home-based care service of the Department of Palliative Medicine, Bangabandhu Sheikh Mujib M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(26 reference statements)
0
3
0
1
Order By: Relevance
“…Vertinant gyvenimo kokybę, itin svarbu objektyvią sveikatos būklę atskirti nuo subjektyvios paciento savijautos [11]. Holistinis paliatyviosios pagalbos požiūris gali pagerinti šių pacientų ir jų šeimų gyvenimo kokybę, užtikrindamas ligos eigą, galutinį gyvenimo etapą ir orią mirtį [2].…”
Section: įVadasunclassified
“…Vertinant gyvenimo kokybę, itin svarbu objektyvią sveikatos būklę atskirti nuo subjektyvios paciento savijautos [11]. Holistinis paliatyviosios pagalbos požiūris gali pagerinti šių pacientų ir jų šeimų gyvenimo kokybę, užtikrindamas ligos eigą, galutinį gyvenimo etapą ir orią mirtį [2].…”
Section: įVadasunclassified
“…Home-based care not only reduces costs compared to inpatient care but also enhances patient outcomes by increasing access to essential care and reducing hospitalizations ( 52 ). Increasing the number of mobile teams would also help address disparities in accessing these services in remote and rural areas, where traditional healthcare facilities may be limited or non-existent ( 9 , 40 , 52 ). Given that the majority of palliative patients in Kazakhstan are cared for by their families, equipping family caregivers with proper training can support them in delivering high-quality home-based care.…”
Section: Recommendationsmentioning
confidence: 99%
“…This leads to an unequal distribution of suffering among patients and their families, especially among those who are economically disadvantaged, socially excluded, or reside in remote and rural regions. Palliative care in LMICs can improve the quality of life of patients and their family caregivers by increasing access to medications essential for pain and symptom management ( 8 , 9 ). Studies in Kenya, India, and Bangladesh found that introducing palliative care services in rural districts led to long-term cost-savings, as patients received home- and community-based care, reducing the need for costly hospitalizations and other healthcare services ( 4 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study of the elderly with an average age of 79 years infers that the QoL of the elderly is positively correlated with receiving home-based primary care [21,22]. And studies take cancer elderly as the research object, assert that the use of home care service of the physical health of old cancer people is better than do not use the home care service of cancer elderly, but below the average [23]. The reasons for the research diversity are as follows:…”
Section: Concept and Development Of Home-based Care Servicementioning
confidence: 99%